Factors Associated with Post-COVID Cardiac Conditions and Potential Prognostic Factors: A Systematic Review - Lidian Franci Batalha Santa Maria; Josicélia Estrela Tuy Batista; Virginia Kagure Wachira; Wenderval Borges Carvalho Junior; Alexandre Anderson de Sousa Munhoz Soares; Isis Polianna Silva Ferreira de Carvalho; Henry Maia Peixoto (Life)
Cardiac conditions are a significant category of post-COVID conditions. The objective of this study was to synthesise the evidence on the factors associated with the development of post-COVID cardiac conditions, the frequency of clinical outcomes in affected patients, and the potential prognostic factors. A systematic review was conducted using the databases EBSCOhost, MEDLINE via PubMed, BVS, and Embase, covering studies from 2019 to December 2023. A total of 8343 articles were identified, and seven met the eligibility criteria for data extraction. The protective effect of vaccination stood out among the associated factors, showing a reduced risk of developing post-COVID cardiac conditions. Conversely, COVID-19 reinfections were associated with an increased risk of cardiovascular outcomes. Regarding the main outcomes in these patients, most recovered, although some cases persisted beyond 200 days of follow-up. The study included in the analysis of prognostic factors reported that the four children who did not recover by the end of the study were between two and five years old and had gastrointestinal symptoms during the illness. The COVID-19 vaccination regimen reduces the risk of developing post-COVID cardiac conditions. Public health policies promoting immunisation should be encouraged to prevent SARS-CoV-2 infections and reinfections.